Late Cretaceous to Cenozoic geodynamic evolution of the Atlantic margin offshore Essaouira (Morocco). (5th May 2015) - Neumaier, Martin; Back, Stefan; Littke, Ralf; Kukla, Peter A.; Schnabel, Michael; Reichert, Christian
Abstract: After Mesozoic rifting, the Atlantic margin of Morocco has recorded the consequences of the continental collision between Africa and Europe and the relative northward motion of the African plate over the Canary Island hotspot during Cenozoic times. Interpretation of recently acquired 2D seismic reflection data (MIRROR 2011 experiment) presents new insights into the Late Cretaceous to recent geodynamic evolution of this margin. Crustal uplift presumably started during the Late Cretaceous and triggered regional tilting in the deep‐water margin west of Essaouira and the formation of the Base Tertiary Unconformity (BTU). An associated hiatus in sedimentation is interpreted to have started earlier in the north (presumably in the Cenomanian at well location DSDP 416) and propagated to the south (presumably in the Coniacian at well location DSDP 415). The difference in the total duration of this hiatus is postulated to have controlled the extrusion of Late Triassic to Early Jurassic salt during the Late Cretaceous to Early Palaeocene non‐depositional period, resulting in regional differences in the preservation of salt structures: the Agadir Basin in the south of the study area is dominated by salt diapirs, whereas massive canopies characterised the Ras Tafelnay Plateau farther north and salt‐poor canopies and weld structures the northernmost offshore Essaouira and Safi Basins. Accompanied by volcanic intrusions, a presumably Early Palaeogene reactivation of previously existing basement faults is interpreted to have formed a series of deep‐water anticlines with associated gravity deformation of shallow‐seated sediments. The orientation of the fold axes is roughly perpendicular to the present day coast and the extensional fault direction; therefore, not a coast‐line parallel pattern of extensional faults, related to the rifting and break‐up of the margin, but rather a coast‐line perpendicular oceanic fracture zone might have caused the basement faults associated with the deep‐water folds. Both the volcanic intrusions and the formation of the deep‐water anticlines show a comparable age trend which gets progressively younger towards the south. A potential tempo‐spatial relationship of the BTU and the reactivation of basement faults can be explained by the relative northward motion of the African plate over the Canary Island hotspot. Regional uplift producing the BTU could have been the precursor of the approaching hotspot during the Late Cretaceous, followed during the Early Palaeogene by a locally more pronounced uplift above the hotspot centre.